HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN PERAWAT DENGAN PENCEGAHAN HEALTHCARE ASSOSIATED INFECTIONS DI INSTALASI RAWAT INAP RS Dr.REKSODIWIRYO PADANG TAHUN 2017 - -, Monna Widyastuti (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Nurse, one of nursing care providers in hospital and 24 hours with patients, requiredto provide nursing care and nursing services that focus on preventing HAIs. HAIs preventiondata is still poor at the. Dr. Reksodiwiryo Hospital Padang (36.8%). The purpose of this studywas to determine the relationship between the characteristics and knowledge of nurses withHAIs prevention in Inpatient Unit at the Dr. Reksodiwiryo Hospital Padang in 2016. The studyused quantitative approach with cross sectional study design. The population was all of nursein Inpatient Unit with 89 people for sample. Data were analyzed by Chi Square test. Theresults of the study were no correlation between age, gender, education level, length of work,and knowledge with the prevention of HAIs. It is expected to improve the supervisory activitiesto the inpatient unit for further so that nurses are not negligent in preventing HAIs.